A Geographical Assessment of The Historical And Tourist Relics of The Akre District and How They Developed - Nechirvan Kh. Abdulhadi; Luqman Weso Omer; Nawshirwan Dawd Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Tourism is one of the activities that is constantly developing, diverse, one of the types is historical and religious archaeological tourism that is considered one of the important principles of tourism Lay Akre, Shush Castle, Akre Great Mosque, Der Mariana, Gundk Cave, etc. The researchers have come to the conclusion that the geographical location of Akre district is rich in archaeological sites, which (116) archaeological sites in the district, which helps tourists to see many different places in a short time ە as Poor or lack of road networks and lack of projects, tourist guides and tourism services that 83.6% of tourists see these problems in the areas. Therefore, more attention should be paid to these areas by the relevant authorities in order to diversify tourism in the study area through the creation of tourist guides and the creation of tourism communities in the historical and religious archaeological areas of Akre district.